Engineering the T6SS of Pseudomonas for targeted delivery of antibacterial and antifungal effectors - Alicia Isabel Pérez-Lorente; Mario Araujo-Garrido; Antonio de Vicente; Diego Romero; Carlos Molina-Santiago (Journal of Biological Engineering)
Abstract Background Bacteria employ diverse molecular systems, such as the type VI secretion system (T6SS) to outcompete other microorganisms and adapt to ecological niches. The T6SS is a versatile nanomachine capable of delivering toxic effectors into neighboring cells, providing advantages in bacterial interactions. In recent years, T6SSs have been proposed as promising tools for engineering selective antimicrobial platforms. Results In this study, we successfully engineered Pseudomonas putida KT2440 to heterologously express and release T6SS effectors. The expression of Tse1, an effector from Pseudomonas chlororaphis, induced sporulation in plant-beneficial Bacillus strains via a T6SS-dependent mechanism, particularly when Tse1 was paired with a PAAR protein. Similarly, the engineered strain effectively inhibited Aeromonas hydrophila growth using the phospholipase toxin TplE from Pseudomonas aeruginosa. Furthermore, antifungal activity was achieved by coexpressing Tfe2, an effector from Serratia marcescens, with VgrGs, resulting in increased reactive oxygen species levels and cellular damage in Botrytis cinerea. Importantly, the T6SS was also employed to deliver non-T6SS effectors such as chitosanase, demonstrating its versatility in degrading fungal cell walls. Conclusions Our findings demonstrate that the T6SS can be engineered to deliver both canonical and noncanonical effectors, providing a robust platform for targeted antibacterial and antifungal applications. The modularity of the system enables precise pairing of effectors with structural components such as VgrG and PAAR proteins, optimizing delivery efficiency. These engineered systems provide new opportunities for the development of biocontrol strategies in agriculture, microbiome modulation, and potential therapeutic applications. Future advancements in bioinformatics and protein engineering will further increase the specificity and functionality of T6SS-based delivery systems, offering innovative tools for managing microbial ecosystems and addressing global challenges in health and agriculture.